P100 The link between angiogenesis and osteogenesis in spondyloarthritis. (21st February 2018) - Kaaij, MH; van Hamburg, JP; Kollias, G; Baeten, D; van Duivenvoorde, L
Abstract : Introduction: Spondyloarthritis is characterised by inflammation, extensive angiogenesis and pathological osteogenesis. Transmembrane (tm) TNF transgenic (tg) mice 1 that overexpress tmTNF exhibit features of SpA, including chronic inflammation and pathological osteogenesis. tmTNF ligation to TNF receptor 2 in endothelial cells (ECs) can induce signal transduction pathways, that may promote these processes. Of note, angiogenesis and osteogenesis are coupled by EC differentiation towards a type H (CD31 hi endomucin hi ) phenotype. 2 Objectives: To investigate the link between pathological angiogenesis and osteogenesis in tmTNF tg mice and the potential contribution of noncanonical NF-κB signalling in ECs to this process and infiltration of immune cells into the bone marrow (BM). Methods: Vertebrae and ankles from 6 and 12 weeks and 8 months old tmTNF tg mice or sex-matched non-tg littermates (n=18) were prepared by cutting 60 µm thick cryosections for confocal imaging. Results: tmTNF tg mice exhibited ectopic osteogenesis which was not observed in non-tg littermates. Immunostainings showed that type H vessels are in the vicinity of the ectopic osteogenesis and osterix + osteoprogenitors. At six weeks of age, osterix + cells are located throughout the ectopic lesion, while at eight months, osterix + cells are only present at the border of the lesion. Furthermore, there is increased osteogenesis and a different vessel architecture within the vertebrae of tmTNF tg mice compared to non-tg littermates that progresses with age. Non-tg littermate vertebrae only have physiological osteogenesis, which is in the metaphysis and periosteum. In addition, tmTNF tg mice also exhibit altered bone marrow (BM) architecture containing extensive lymphoid aggregates, which predominantly consisted of B220 + B cells. Conclusions: tmTNF overexpression in mice leads to development of type H vessels associated with ectopic osteogenesis. In addition, extensive lymphoid aggregates develop in the BM. Current studies are aimed at identification of signalling pathways in ECs that contribute to these processes. References: . Alexopoulou L, et al. Eur J Immunol1997;27(10):2588–92. . Kusumbe AP, et al. Nature2014;507(7492):323–328. Disclosure of interest: None declared